Principles of management of women with hirsutism - a dermatologist's perspective - Dominik Mikiel; Barbara Olszewska; Adriana Polańska; Zygmunt Adamski; Ryszard Żaba; Aleksandra Dańczak-Pazdrowska (Termedia Publishing House, 2020)
Hirsutism is a common clinical diagnosis defined by the presence of excess growth of terminal hair in androgen-sensitive areas. It affects 5-15% of women, often having a significant impact on their daily functioning. Hirsutism is mainly caused by ovarian or adrenal hyperandrogenism, although it can be idiopathic, drug induced or caused by other endocrinopathies. Severity of the disease can be assessed using a modified Ferriman-Gallwey visual scoring scale. Therapeutic options include hair removal using lasers or electrolysis, combined oral contracetion, antiandrogens and topical eflornithine. This article presents a clinical scheme for diagnosis and management of hirsutism from a dermatological perspective.